UPAYA MENJADIKAN MADRASAH SEBAGAI LEMBAGA PENDIDIKAN UNGGUL - Hasan, Muhammad Nur (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractEfforts Muslims to realize the quality of Islamic Education Institutions have long coveted, to be able to give birth to a superior madrasah model that can compete with general education institutions.Madrasah on behalf of himself as superior schools and madrasah model should be recognized by the government and the public, not by the madrasah / school itself. Because excellence means having a value more than the other schools or Madrasahs, and certainly worth it not only can be seen from the physical aspect, but also other aspects that determine.Characteristics of a superior madrasah at least has three aspects, 1). Input, how the selection process for potential students is be done. 2) The process, which includes the ability of teachers, adequate facilities learning, curriculum, skill for language of Indonesian, Arabic, and English is absolutely necessary, teaching methods, which make students become active and creative, which is accompanied by freedom in expressing thoughts and imagination, also extar activities program, as well as extensive cooperation network. 3) Out put, an ability of graduates produced deemed superior, when they have been able to develop intellectual, emotional and spiritual potention of where they are located.Therefore, madrasah should have the advantage to be proud of the school and the community, which includes comparative advantage and competitive advantage. Keywords: Islamic Education, Madrasah, Superior,